DNA methylation screening identifies driver epigenetic events of cancer cell survival - De Carvalho, Daniel D. (2012)
Cancer cells typically exhibit aberrant DNA methylation patterns that can drive malignant transformation. Whether cancer cells are dependent on these abnormal epigenetic modifications remains elusive. We used experimental and bioinformatics approaches to unveil genomic regions that require DNA methylation for survival of cancer cells. First, we surveyed the residual DNA methylation profiles in cancer cells with highly impaired DNA methyltransferases. Then, we clustered these profiles according to their DNA methylation status in primary normal and tumor tissues. Finally, we used gene expression meta-analysis to identify regions that are dependent on DNA methylation-mediated gene silencing. We further showed experimentally that these genes must be silenced by DNA methylation for cancer cell survival, suggesting these are key epigenetic events associated with tumorigenesis.